The development of PhD students writing skills: academic essay writing at English lessons - Rezunova, Olena; Резунова, Олена Сергіївна (Центр міжнародного наукового співробітництва, видавництво "ТК Меганом ", 2020)
Writing is one of the four types of language skills which forms a person's communicative system and ensures its social and cultural existence. The purpose of this study is to analyze the ways to develop of PhD students writing skills at English lessons. The study analyzed the structure and basic requirements for writing an academic essay. A set of exercises for developing academic essay writing skills is offered. It is proved that writing an academic essay contributes not only to the development of students' written competence but also to their professional development. Письмо – один із чотирьох видів мовленнєвої діяльності, що формує комунікативну систему людини і забезпечує її різноманітне соціокультурне буття. Мета цього дослідження - проаналізувати шляхи розвитку навичок письма здобувачів ступеня доктора філософії на уроках англійської мови. В ході дослідженя було проаналізовано структуру та основні вимоги до написання академічного есе. Запропоновано комплекс вправ на відпрацювання навичок написання академічного есе. Доведено, написання академічного есе сприяє не лише розвитку письмової компетентності студентів, а й їх професійному розвитку.
Розвиток навичок письма здобувачів ступеня доктора філософії: написання академічного есе
Keywords: writing skills; навички письма; PhD students; здобувачі степеня доктора філософії; academic essay; академічне есе